Peripheral nerves electrostimulators. Technical Specifications - Domeracki, Mateusz; Braun, Agnieszka; Kożuchowski, Marcin; Prylińska, Monika; Skierkowska, Natalia; Husejko, Jakub; Szmelcer, Beniamin; Trzebiatowska, Agata; Wilczyński, Michał (Journal of Education, Health and Sport, 2018)
Admission The first successful attempt to use stimulants neuro modulation properties date back to the first half of the twentieth century. Due to the high technological limitations, the use of peripheral nerve electrostimulators the early eighties XX century was relatively small and involved few patients treated primarily due to neuropathic pain and patients psychosurgical.The development of modern batteries in the eighties of the twentieth century, standardization and implementation process to achieve consensus on the guidelines for operations in the field of functional neurosurgery, they contributed to intensified "Renaissance" functional neurosurgery.Material and methods Articles in the EBSCO database were analyzed using the keywords: peripheral nerves, stimulation, electrostimulation, neurosurgery. Furthermore, neural searched betting sites in terms of the technical aspects of this equipment. Available literature was subjectively selected. Then searched the latest version of each article.Results Offered different tools offered technical specifications. Technological developments have allowed the convenience to use devices, min. by increasing control by the user or representative of the operation of the pacemaker.Conclusions The development of technology and neuroscience neurostymulatorów resulted in the development of many available on the market. However, more research is needed to determine the exact parameters of stimulation, which would get the largest size stimulation effect while minimizing adverse effects.